Assessment of immersed boundary method as a tool for direct numerical simulation of aeroacoustic sound - Kosei NISHIKAWA; Kodai KONNO; Yuji HATTORI (Journal of Fluid Science and Technology, 2020)
An immersed boundary method of discrete type is tested as a tool for direct numerical simulation of aeroacoustic sound. The numerical method consists of the WENO scheme, the immersed boundary method by Chaudhuri et al. (J. Comp. Phys. Vol. 230, 1731–1748 (2011)), and the perfectly matched layer together with the dyadic mesh refinement and the Runge-Kutta method. The accuracy of the method is shown to be sufficient for four basic problems: propagation of acoustic waves, aeroacoustic sound generation in a flow past a fixed circular cylinder, in a flow past an oscillating square cylinder, and from a vortex pair passing through a circular cylinder. The results confirm that the developed method can deal with moving bodies and it is accurate not only for viscous flows but also for inviscid flows.